From the maxim of Know thyself at all times: On the question of religious self-criticism in Islam - Karimi, Ahmad Milad; Hamdan, Ali (Münster journal for Islamic and philosophical studies, 2022)
Although the cultural and spiritual meaning of the religion of Islam is in deep crisis, it is not possible to talk, according to the author, about the rigidity of the Islamic spirit. The internal capabilities of Islam, represented in the close connection with the reason and the motivation for rational religious criticism of the self, can only be understood in the context of the culture of enlightenment, bearing in mind that the discussion here is not about a specific enlightenment or an enlightenment era with a Christian character, but rather about the culture of enlightenment. Revelation is defined in the Qur’an as a logical, moral, and even aesthetic criterion al-furqān. Here, Islam is understood as the path of happiness, which leads human to enlightenment related to himself, the meaning of his existence and his destiny. However, the contents of revelation are not always clear; rather, revelation as the Criterion makes the believers the only ones who draw the features of religion through their interpretations, based mainly on the principle of rational evaluation to ensure its reasonableness and permanence of criticism. The meaning of faith in Islam is the internal treatment of religion itself, which happens in a third place, in which religious understanding is defined as a constant pursuit of knowledge and an inability to grasp the absolute truth [Ali Hamdan].